Growth, feeding practices, and haemoglobin levels in 6 to 12 month-old infants exposed and unexposed to maternal HIV status in a peri-urban area in Gauteng province, South Africa - Hoffman, Marinel (University of Pretoria, 2024)
Thesis (PhD Food Science (Nutrition))--University of Pretoria, 2024.